Effects of Photobiomodulation and Ultrasound Applications on Orthodontically Induced Inflammatory Root Resorption; Transcriptional Alterations in OPG, RANKL, Cox-2: An Experimental Study in Rats - Amuk, Nisa Gul; Kurt, GÖKMEN; KURT, GÖKMEN; Güray, Enis (My University, 2018)
Objective: The aim of this study was to evaluate and compare the reparative and inhibitory effects of a light-emitting diode-mediated photobiomodulation (PBM) and of a low-intensity pulsed ultrasound (LIPUS) on orthodontically induced inflammatory root resorption (OIIRR). Materials and methods: Forty-nine Wistar rats were divided into four groups: untreated group (negative control), group treated with orthodontic appliances (positive control), PBM-treated group (wavelength: 618 nm, output power density: 20 mW/cm(2)), and LIPUS-treated group (frequency: 1.5% +/- 5% MHz, pulse repetition ratio: 1.0% +/- 10% kHz, effect area: 3.88% +/- 1% cm(2) and intensity: 30% +/- 30% mW/cm(2)). OIIRR was induced experimentally in rats for 14 days with an applied force of 100g, and therapeutic approaches were performed concurrently. At the end of the experiment, upper first molar teeth of rats were prepared for genetic analysis, scanning electron microscopy, hematoxylin and eosin staining, and tartrate-resistant acid phosphatase staining. Kruskal-Wallis and post hoc Dunn-s tests were performed. Results: Number of osteoclasts (p < 0.01), number of resorption lacunae and resorption area ratio (p < 0.001) decreased and number of total cells (p < 0.001) increased with the PBM and LIPUS applications when compared with the positive control group. Receptor activator of nuclear factor kappa B ligand (RANKL) levels of PBM and LIPUS groups were lower (p < 0.001), and osteoprotegerin (OPG) levels were higher (p < 0.001) than the positive control group. Cyclooxygenase-2 (Cox-2) expression significantly decreased with LIPUS and PBM administrations (p < 0.05). No significant difference was observed among PBM and LIPUS groups. Conclusions: PBM and LIPUS applications showed marked inhibitory and reparative effects on OIIRR by modulating the OPG/RANKL ratio, Cox-2 expression, and cell differentiation of osteoblasts and osteoclasts.